Advances in poultry nutrition - JAIN, ARCHANA (The Indian Journal of Animal Sciences, 2021)
In the fast-developing poultry sectors of Asia, particularly in India, it is thought that the elevated levels of poultry feed will be required for fast development of the poultry sector, in particular, to meet the highest consumer demand for poultry products. The significant increase in feed demand will be associated with increased outputs of formulated compound feeds. Globally, few protein and energy ingredients are being used in the manufacture of poultry feed for landless and large-scale commercial operations, with a significant reliance on soybean and traditional cereal grains to achieve nutrient supply and balance. The feed versus fuel debate over cereal usage is continued, which will have impact on feed and livestock production levels, and also on feed-industry dynamics. New and refined technologies are now being used by using ethanol by-products with good amounts of nutritional characteristics—for example, dried distillers’ grains with solubles (DDGS) in the future, parallel to the economic evaluation and justification of such products with respect to competitor feed ingredients. This review article discusses the importance and growth of the poultry sector along with nutritional research efforts in the 21st century.